'Like doing a jigsaw with half the parts missing': community pharmacists and the management of cancer pain in the community. (9th October 2012) - Savage, Imogen; Blenkinsopp, Alison; Closs, S. Jose; Bennett, Michael I.
Abstract Objectives The aim was to explore and describe community pharmacists' current and potential place in the cancer pain pathway. Objectives were to describe pharmacists' role in advising patients and their carers on optimum use of opioid drugs for pain relief, identify elements of medicines management that could be modified and identify opportunities for improved communication with patients and other professionals. Methods Semi‐structured interviews were conducted with 25 community pharmacists in three areas of England. Data were analysed using the Framework method. Key findings Pharmacists had no reliable method to identify patients with cancer and no access to disease stage and treatment plan information. There was little evidence of any routine communication with other professionals about patient care. Contact with patients was limited. Access to palliative care medicines could be problematic for patients and medicines use reviews (MURs) were rarely done. Interview data suggested variable levels of knowledge about optimal opioid use in cancer pain or awareness of patients' priorities. For some pharmacists, proactive involvement appeared to be inhibited by fear of discussing emotional and wider social aspects and accounts showed that a wide range of issues and concerns were raised by family members, indicating considerable unmet need. Pharmacists tended to assume information had already been provided by others and felt isolated from other care team members. Many felt that their potential contribution to cancer pain management was constrained but aspired to do more. Conclusions There is significant scope for improving access to and interaction with, community pharmacists by people with cancer pain and their families. Finding ways to embed pharmacists within palliative care teams could provide a starting point for a greater contribution to cancer pain management.